Do Sítio Caboclo ao assentamento Nossa Senhora das Graças: território de exploração versus território de esperança - Silva, Manoel Vieira da (2011)
This thesis studies the changes that took place in the municipality of Bananeiras, specifically in the property known as Farm Caboclo with its transformation into a Settlement Project of agrarian reform. It seeks to understand if this new territory breaks with the logic of capitalist domination and represents the transformation of an area of exploitation in a territory of hope. The study used as instruments: bibliographic and documentary research and a survey of secondary data and field research. The thesis is divided into four chapters besides the introduction and final consideration. The first chapter studies the territorial formation and organization of the agrarian space of the municipality of Bananeiras where is located the former property of Farm Caboclo . The second chapter describes the issue of land in the municipality; emphasizes the struggle for land and formations of rural settlements. The third chapter describes the forms of production and work organization and power relations in the former Farm Caboclo . The fourth chapter presents the process of formation of the Settlement Project Nossa Senhora das Graças and its form of territorial organization. In the final consideration there is a reflection on the contradictions in the process of building a territory of hope based on this study.